EFFECTS OF A PROGRAM OF INTERVENTION ON LEVELS OF PHYSICAL ACTIVITY AND LIFESTYLE IN SPECIAL POPULATION. (Fiep Bulletin - online, 2011)
Physical inactivity is increasing in an epidemic way, directly reflected in increased rates of morbidity and mortality from chronic degenerative diseases. Surveys of the World Health Organization suggest that physical inactivity alone accounts annually for approximately two million deaths worldwide. The population with a disability, particularly with intellectual disability (ID), have low levels of physical activity. Objective: To evaluate the effect of an intervention program on physical activity levels of physical activity and lifestyle of young people and adults with intellectual disabilities. Methods: The sample comprised 70 people of both genders aged between 18 and 35 divided by age and gender. This is an intervention study, conducted over a year about the effect of a program to promote physical activity and lifestyle evaluated by questionnaires and physical tests. Physical activity was proposed based on the recommendations of the American College of Sports Medicine (ACSM) at least 30 minutes of physical activity on most, preferably all days of the week. The activity performed during these 30 minutes were walking and stretching exercises. For analysis of data was used in addition to basic statistical analysis of variance (ANOVA) was used for comparison between groups and the difference between the groups means the technique of Scheffé. We calculate the values of "p" (p < 0.05). Results: Group 1, the younger students, no difference between himself but .39 when compared with group 2 (29 to 35 years) all levels of physical activity were statistically significant
Keywords: intellectual disability; physical activity and lifestyle